2015
DOI: 10.1684/epd.2015.0741
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy of infancy with migrating focal seizures: three patients treated with the ketogenic diet

Abstract: Aim. We present three patients with epilepsy of infancy with migrating focal seizures treated with the ketogenic diet. Methods. Between February 1, 2012 and January 31, 2014, three patients who met the diagnostic criteria for migrating focal seizures in infancy at our department were placed on the ketogenic diet and followed for a minimum of seven months. Results. Two of the three children responded well to the ketogenic diet. One of these patients became seizure‐free and his neuropsychological performance als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…One of two patients with MFSI became seizure free at 3 months, whereas the other patients started to show seizure reduction after 3 months but eventually discontinued the diet due to an adverse event (gastric disturbance). These results are similar to those of Caraballo et al [30]. However, the KD response was low in EME, unclassified generalized epilepsy, and unclassified focal epilepsy.…”
Section: Discussionsupporting
confidence: 91%
“…One of two patients with MFSI became seizure free at 3 months, whereas the other patients started to show seizure reduction after 3 months but eventually discontinued the diet due to an adverse event (gastric disturbance). These results are similar to those of Caraballo et al [30]. However, the KD response was low in EME, unclassified generalized epilepsy, and unclassified focal epilepsy.…”
Section: Discussionsupporting
confidence: 91%
“…Preliminary experience also showing some beneficial effects of the KD has been reported in epileptic encephalopathies such as Lafora body disease, 58 Rett syndrome, 59,60 Landau-Kleffner syndrome, 61 and subacute sclerosing panencephalitis ( Table 2). 62 Single reports describe the use of the diet in metabolic disorders such as phosphofructokinase deficiency, adenylosuccinate lyase deficiency, and glycogenosis type V. [63][64][65] Other conditions with limited data include juvenile myoclonic epilepsy, 66 CDKL5 encephalopathy, 67 epilepsy of infancy with migrating focal seizures, 68 childhood absence epilepsy, 69 and epileptic encephalopathy with continuous spike-and-wave during sleep. 70 All of the above strong and moderate indications have sufficient data in our guideline group's opinion to justify the use of KDT.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…Adenylosuccinate lyase deficiency 64 CDKL5 encephalopathy 67 Childhood absence epilepsy 69 Cortical malformations 73,74 Epilepsy of infancy with migrating focal seizures 68 Epileptic encephalopathy with continuous spike-and-wave during sleep 70 Glycogenosis type V 65 Juvenile myoclonic epilepsy 66 Lafora body disease 58 Landau-Kleffner syndrome 61 Lennox-Gastaut syndrome 26 Phosphofructokinase deficiency 63 Rett syndrome 59,60 Subacute sclerosing panencephalitis (SSPE) 62 Long-chain fatty acids are transported across the mitochondrial membrane by carnitine, facilitated by carnitine palmitoyltransferase (CPT) I and II and carnitine translocase. 71 Once in the mitochondrion, fatty acids are b-oxidized to 2-carbon units of acetyl-CoA that can then enter the tricarboxylic acid cycle and be used for energy.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…in a small group of infants (13.8 ± 5.7 months) showed that a ketogenic diet was effective and safe [ 85 ]. Other reports have reported the use of a ketogenic diet in young patients (less than 2 years) [ [86] , [87] , [88] , [89] , [90] , [91] , [92] , [93] , [94] , [95] ]. Most of the patients had infantile spasms and received ketogenic diet therapy during the chronic stage.…”
Section: Use Of a Ketogenic Diet In Nicusmentioning
confidence: 99%